SPATIAL CONCENTRATION OF GEOMORPHOLOGICAL HERITAGE ELEMENTS IN GUARITAS DO CAMAQUÃ GEOMORPHOSITE (RIO GRANDE DO SUL – BRAZIL) - Roxo Madeira, Márlon; Correa, Edvania Aparecida; Simon, Adriano Luís Heck (Revista Brasileira de Geomorfologia, 2021)
Geomorphological mapping of geomorphosites should allow the identification and characterization of the landforms that comprise the geoheritage of these places and demand actions of geoconservation and geotourism. The objective of this study was to identify and analyse the areas with the largest spatial concentration of landforms that comprises the geomorphological heritage elements in Guaritas do Camaquã geomorphosite – Rio Grande do Sul state – Brazil. Using as the starting point the geomorphological map (1:50,000) produced by Santos (2016), the following methodological procedures were performed: (a) selection of the vector data from the geomorphological map and their conversion to raster data; (b) classification of raster data regarding the values of spatial concentration of the geomorphological features into null, very low, low, medium, high and very high; (c) individualization and reclassification of the very high and high values of spatial concentration of the geomorphological features (given value 1), and the other values (given value 0); and (e) overlap of information with value (1) to verify the spatial coexistence of areas with high concentration of geomorphological features. The results allowed to identify the location and the extension of the areas where high concentrations of geomorphological features coexist, and to identify the geomorphological heritage elements that demand priority in geoconservation actions. Some of these geomorphological heritage elements are already part of geotouristic routes, as Pedra das Guaritas, while others are isolated and little explored. Such spatial arrangements of the landforms must be incorporated to the geotouristic routes to integrate the geomorphological heritage elements present in the geomorphosite.